Behavioural adaptation: A review of adaptation to workplace heat exposure of kitchen workers with reference to gender differences in Durban - Gangiah, Sasi (HTS teologiese studies, 2021)
The article examines the gender disparities as women are at a greater risk to exertional heat illness that may go unreported in the industry, according to several reports. It is important to study the behavioural heat adaptations and prevalent behaviours for workers in order to understand the magnitude of the danger they face. Cooking is considered a safe occupation, but hazards certainly do exist and can represent a risk to the health and safety of the workers. Controls can be established to reduce the risk of illness. To attract and retain workers, the food service business must provide a good quality of life.Contribution: The study suggests how female workers in the catering establishments can adjust their behaviour to improve their experience at work. Are women more vulnerable to environmental parameters? Christian theology provides women equal status with men (Kategile 2020), however there are traces of androcentric aspects within the Bible. Women’s involvement in development is based on the theological premise that true development must have a holistic approach towards human development (Onwunta 2009). However, Sibani (2017) stated that the role of God or a creator of a religion, is always taken by a male and a woman’s place is in the household. The article conducts a comprehensive analysis of the literature on the various behavioural adaptation mechanisms used by kitchen staff to cope with heat exposure at work. Thermal tolerance variations are becoming more pronounced because of ethnicity and cultural differences. Health interventions and enhanced work performance are important objectives of workplace safety. Regulated heat in the workplace can be factored into the theory concerning the relationship between gender differences and contextual components. This would increase female food service workers’ understanding of thermal comfort, which is beneficial to productivity efficiency, worker satisfaction and well-being of workers.